1996
DOI: 10.1136/vr.138.5.105
|View full text |Cite
|
Sign up to set email alerts
|

Transient metabolic hyperammonaemia in young Irish wolfhounds

Abstract: Inherited portosystemic shunts occur in 2 to 3 per cent of Irish wolfhounds and are associated with high venous ammonia concentrations and signs of hepatic encephalopathy. Moreover, the vast majority of Irish wolfhound pups without signs of hepatic encephalopathy have moderate hyperammonaemia. The aim of this study was to investigate whether the increased ammonia levels in these clinically healthy dogs are caused by low-grade portosystemic shunting, and whether the hyperammonaemia persists in adulthood. The fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
17
2

Year Published

2004
2004
2013
2013

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 12 publications
2
17
2
Order By: Relevance
“…1996). Transient HA has been reported in Irish wolfhound pups and a similar syndrome has been observed in a mature German Shepherd dog (Meyer et al . 1996; Lobetti et al .…”
Section: Discussionsupporting
confidence: 70%
“…1996). Transient HA has been reported in Irish wolfhound pups and a similar syndrome has been observed in a mature German Shepherd dog (Meyer et al . 1996; Lobetti et al .…”
Section: Discussionsupporting
confidence: 70%
“…However, it has been noted that a proportion of the screened dogs reveal a transient hyperammonemia phase of up to several months, in the absence of portosystemic shunting. 6 It was suggested that this might imply a breed-associated metabolic cause for hyperammonemia. The aim of the current study was to further characterize the previously observed transient hyperammonemia in Irish Wolfhounds and elucidate the responsible inborn error of metabolism.…”
mentioning
confidence: 99%
“…5 The etiopathogenesis of CPSSs is obscure, except that left-sided intrahepatic CPSSs are believed to represent persistence of the ductus venosus. 11,12 Less common causes of hyperammonemia in dogs include transient physiologic hyperammonemia in healthy Irish Wolfhound pups 13 and conditions in which urine that contains ammonia as a result of the activity of urea-splitting microorganisms is absorbed into the systemic circulation. This could happen in dogs with a ruptured urinary bladder or urethra 14 or after surgical ureterocolonic anastomosis.…”
mentioning
confidence: 99%
“…26 In addition, ultrasound-guided core biopsy of the liver was performed, and specimens were submitted for histologic examination.…”
mentioning
confidence: 99%